Produção de presença no contexto da comunicação ubíqua : relações de complexidade entre corpo, tecnologia e ambientes digitais - Oikawa, Erika (2016)
This work aims to comprehend how the materialities of digital media are transforming the way of the body produces presence in the context of ubiquitous communication. Given the centrality of the body in this process, we have chosen as an empirical object of this research the contemporary wellness practices, specifically those dedicated to the weight loss process, due to the ease of tracking them in digital environments. Three routes are conducted to achieve this goal. The first one, with its theoretical epistemological nature, promotes dialogue between the theory of Materialities of Communication, from the work of Hans Ulrich Gumbrecht, and the thought of Complexity, proposed by Edgar Morin, in order to understand the implications of the production of presence phenomena in the digital context. From this articulation, arises the need to consider a new form of inhabiting which emerges with the digital networks, based on information flow and trans-organic forms, toward what Massimo Di Felice calls “atopic experience”. The second route, dedicated to theoretical-methodological level, details the methodological procedures adopted in the research, which had as great challenge the assembly of a corpus that would allow the analysis of the transformations of weight loss practices in digital media over 15 years, seeking to contemplate the transition from fixed internet to mobile internet. To do so, we searched on Google itself these documents, taking advantage of the Internet’s website possibility to make the past present again, and conducted a content analysis of 227 materials with the assistance of Nvivo10, a qualitative data analysis software. In the third route, dedicated to the interpretation of results, we presented how each technological materiality identified in the study – desktops, smartphones, wearable devices and "smart" thing – has been restructuring the informational ecosystem of wellness practices over the years, resulting in changes in cognitive and affective, communicative and interactional processes. We concluded at the end of these three routes that the digital technologies operate to transform the body's insistent materiality into increasingly continuous information flow – from texts on blogs to “real time” monitoring of mobile applications. This process, far from signifying the demise of presence phenomena, represents the setup of new forms of production of presence, in this new landscape we inhabit, trans-organic and post anthropocentric.